Eugenia uniflora Effects on the Depressive-like Behavior of MPTP-Exposed Female Rats: Apoptosis and α-Synuclein Modulation - Anne Suély Pinto Savall; Jhuly Dorneles De Mello; Eduarda Monteiro Fidelis; Vandreza Cardoso Bortolotto; Mustafa Munir Mustafa Dahleh; Gustavo Petri Guerra; Marina Prigol; Robson Puntel; Jean Ramos Boldori; Cristiane Casagrande Denardin; Tuane Bazanella Sampaio; Simone Pinton (Brain Sciences)
Background: Parkinson’s disease (PD) is a neurodegenerative disorder marked by motor deficits and non-motor symptoms, such as depression, which are associated with dopaminergic loss and α-synuclein aggregation in the brain. Objectives: This study investigated the neuroprotective effects of a hydroalcoholic extract of the purple fruit of Eugenia uniflora (PFEU) on motor ability and depressive-like behaviors in a PD model induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) in female Wistar rats. Methods: Rats received intranasal administration of MPTP or vehicle, followed by 14 days of oral administration of PFEU (300 or 2000 mg/kg, administered once daily) or vehicle. Depressive-like behavior was assessed using the splash and forced swimming tests, while motor ability was evaluated using the rotarod and open field tests. On day 15, hippocampal tissue was collected for immunoreactivity analysis. Results: MPTP treatment induced depressive-like behavior, which was significantly reversed by PFEU, as evidenced by increased grooming and decreased immobility. No motor coordination or locomotion deficits were observed. Furthermore, PFEU treatment prevented the MPTP-induced increase in hippocampal α-synuclein, p-p53, and Bax while restoring Bcl-2 levels, suggesting neuroprotective effects through the modulation of apoptotic pathways and α-synuclein. Conclusions: These findings support PFEU’s potential as a neuroprotective agent for MPTP-induced depressive-like behavior in female rats, highlighting its molecular mechanisms.